Which is the optimal antiobesity agent for patients with nonalcoholic fatty liver disease? - Tsankof, Alexandra; Neokosmidis, Georgios; Koureta, Evgenia; Veneti, Stavroula; Cholongitas, Evangelos; Tziomalos, Konstantinos (Frontiers in Endocrinology, 2022)
Nonalcoholic fatty liver disease (NAFLD) is the commonest chronic liver disease and affects a considerable proportion of the general population worldwide. Obesity is a major risk factor for development and progression of NAFLD and weight loss is an effective intervention for the management of NAFLD. However, few patients achieve substantial and sustained weight loss with lifestyle measures. Therefore, antiobesity agents are frequently considered in patients with NAFLD but there are limited data on their safety and efficacy. In the present review, we discuss the role of antiobesity agents in the management of NAFLD. All approved antiobesity agents appear to reduce transaminase levels and to improve steatosis in patients with NAFLD. However, their effects on fibrosis are less well studied and whether they affect liver-related outcomes, including progression to cirrhosis and hepatocellular cancer, is unknown. The glucagon-like peptide-1 receptor agonists, liraglutide and semaglutide, appear to represent a first-line option in obese patients with NAFLD and type 2 diabetes mellitus (T2DM) since they induce considerable weight loss and have been extensively studied in patients with T2DM. However, more studies are needed to evaluated their effects on liver-related and cardiovascular outcomes in patients with NAFLD, particularly in those without T2DM.